Does the absence of human sellers bias bidding behavior in auction experiments? - Björn Bartling; Tobias Gesche; Nick Netzer (University of Zurich, Department of Economics, 2016)
This paper studies the impact of the presence of human subjects in the role of a seller on bidding in experimental second-price auctions. Overbidding is a robust finding in second- price auctions, and spite among bidders has been advanced as an explanation. If spite extends to the seller, then the absence of human sellers who receive the auction revenue may bias upwards the bidding behavior in existing experimental auctions. We derive the equilibrium bidding function in a model where bidders have preferences regarding both, the payoffs of other bidders and the seller's revenue. Overbidding is optimal when buyers are spiteful only towards other buyers. However, optimal bids are lower and potentially even truthful when spite extends to the seller. We experimentally test the model predictions by exogenously varying the presence of human subjects in the roles of the seller and competing bidders. We do not detect a systematic effect of the presence of a human seller on overbidding. We conclude that overbidding is not an artefact of the standard experimental implementation of second-price auctions in which human sellers are absent.
Keywords: C91; D03; D44; D82; 330; second-price auction; spite; overbidding; laboratory experiments